Long-Term Effects of a Multimodal Physiotherapy Program on the Severity of Somatosensory Tinnitus and Identification of Clinical Indicators Predicting Favorable Outcomes of the Program - Côté, Claudia; Baril, Isabelle; Morency, Catherine-Ève; Montminy, Samuel; Couture, Mélanie; Leblond, Jean; Roos, Marianne; Roy, Jean-Sébastien (Journal of the American Academy of Audiology, 2019)
Tinnitus, the perception of sound in the absence of external auditory stimuli, is commonly associated with problems of the auditory system. Head and neck disorders can also be involved in tinnitus emergence. In such cases, the term somatosensory tinnitus is used. Physiotherapy treatments have been identified as a promising avenue in the treatment of somatosensory tinnitus.The aim of the study was to explore the effect of a physiotherapy program on the intensity and severity of somatosensory tinnitus and to identify the clinical characteristics of the patients who respond well to this treatment.Quasi-experimental pre–post single-group design.Thirty-one adults with presumed somatosensory tinnitus.All participants received on average ten physiotherapy treatments over six weeks. Treatments included cervical and thoracic mobilizations, as well as muscular strengthening, stretching, postural instruction, and cervical stabilization.Outcomes were measured at baseline, at the end of the physiotherapy program, and three months later. The primary outcomes were the Tinnitus Handicap Inventory and visual analog scales for loudness and annoyance caused by tinnitus.After the last evaluation, participants were divided into two groups: improved and unimproved participants. Participants were considered improved if they (1) showed significant improvement in at least two of the three primary outcome measures and (2) indicated subjective improvement. Thereafter, the baseline characteristics that correctly identify participants susceptible to improve significantly following treatment were determined (Cohen’s effect size d > 0.8).A significant improvement in tinnitus intensity was observed at the end of the program. Of the 31 participants, 14 experienced persistent improvement in the intensity of their tinnitus and were classified as improved. Baseline characteristics strongly associated with tinnitus improvement were no increase in tinnitus when exposed to noise (d = −1.57), no family history of tinnitus (d = −1.16), somatosensory modulation in response to the contraction used to resist pressure applied to the forehead (d = 1.20), and recent onset of tinnitus (d = 1.03).This exploratory study showed that a multimodal physiotherapy program is effective in decreasing the severity of tinnitus, principally in individuals presenting with somatosensory tinnitus in combination with specific clinical characteristics.
Keywords: cervical dysfunction; exercises; manual therapy; somatosensory tinnitus